Step by step pediatric echocardiography - Gera, Rani; Sachdev, HPS (New Delhi : Japee Brothers Medical Publishers, 2010)
This concise step-by-step guide and the accompanying CD-ROM provide those just beginning to work in the echo lab with the basic information concerning the diagnostic interpretation of the echocardiograph.
Esta guía concisa paso a paso y el CD-ROM adjunto brindan a aquellos que recién comienzan a trabajar en el laboratorio de ecografía la información básica relacionada con la interpretación diagnóstica del ecocardiógrafo.
Contents 1. Introduction 2. Positions, Patterns and Transducers 3. M-Mode and Doppler Examination 4. Echocardiographic Evaluation of Cardiac Chambers.Left ventricle 5. Acyanotic Congenital Heart Disease. y otros 5 capítulos más Chapter 2: Pulmonary Anatomy and Physiology Chapter 3: Respiratory Pathophysiology 4: Arterial Blood Gas Analysis Chapter 5: Indication for Mechanical Ventilation y otros 9 capítulos más
Keywords: CARDIOLOGÍA PEDIÁTRICA; ECORDIOGRAFÍA; CORAZÓN -- ENFERMEDADES -- DIAGNÓSTICO